Artificial Intelligence on ELT for Literature Studies - Rizkia Shafarini; Ice Sariyati; Andang Saehu (Institut Agama Islam Negeri Palopo, 2023)
Technology has advanced at a rate never before seen in the 21st century, with artificial intelligence (AI) emerging as one of the most significant developments of our time. This rapid integration of AI into various aspects of our lives has not spared the realm of education, particularly English Language Teaching (ELT). Literature studies have traditionally been characterized by the human-centric approach, where educators and scholars engage in close readings, discussions, and interpretations of literary works. However, the advent of AI technologies has introduced a paradigm shift, redefining how literature is taught, analyzed, and appreciated. The intersection of Artificial Intelligence (AI) and English Language Teaching (ELT) within the context of literature studies is a dynamic and evolving field that has garnered increasing attention in recent years. The research is conducted to investigate and understand how artificial intelligence (AI) impacts English language teaching (ELT) in the context of literature studies. The researcher employed a qualitative research approach for this investigation. A naturalistic setting is used in qualitative research, which focuses on analyzing contemporary phenomena using diverse techniques like interviews, observations, and literature studies. The result of this study that artificial intelligence's (AI) influence on English language instruction (ELT) in the context of literary studies reveals a complicated and dynamic terrain.Â